(untitled) (Eurasian Journal of Learning and Academic Teaching, 2026)
This study aims to provide an in-depth description of the implementation of the inquiry learning method in Natural and Social Science (IPAS) learning at SD Negeri 2 Pulau Maitara, Tidore Kepulauan City, North Maluku. The background of this research is the low student learning activeness and weak conceptual understanding of IPAS material due to the dominance of conventional teacher-centered learning methods. The study employed a descriptive qualitative approach involving 24 fourth-grade students, one classroom teacher, and the school principal as research subjects. Data collection was carried out through participatory observation over 12 sessions, semi-structured in-depth interviews, and documentation. Data analysis applied the Miles, Huberman, and Saldana (2014) model, covering data condensation, data presentation, and conclusion drawing. Data validity was tested through source triangulation, technique triangulation, and member checking. The results show that inquiry learning was implemented in a structured manner through five stages: orientation, problem formulation, hypothesis formulation, data collection, and conclusion drawing. The utilization of the natural environment of Maitara Island as a contextual learning resource was the key advantage of this implementation. Findings reveal an increase in student activeness from 42.3% to 78.3%, and an increase in the average conceptual understanding score from 62.4 (low category) to 79.8 (high category). Major constraints identified include limited laboratory facilities, unstable internet connectivity, and students’ habitually passive learning behavior. This study contributes to the development of a contextual learning model based on local island potential that is adaptive to infrastructural limitations in Indonesia’s remote island areas